Two Vanilloid Ligand Bindings Per Channel Are Required to Transduce Capsaicin-Activating Stimuli - Liu, Ting-Yi; Chu, Ying; Mei, Hao-Ruei; Chang, Dennis; Chuang, Huai-Hu (Frontiers in Molecular Neuroscience, 2020)
The tetrameric capsaicin receptor TRPV1 in mammals has evolved the capability to integrate pain signal arising from harmful temperature and chemical irritants. The four repetition of TRPV1 subunits result in an ion channel with excellent pain sensitivity, allowing this ionotropic receptor to differentiate graded injuries. We manipulated the stoichiometry and relative steric coordination of capsaicin-bound structures at the molecular level to determine the rules by which the receptor codes pain across a broad range of intensities. By introducing capsaicin-insensitive S512F mutant subunits into the TRPV1 channel, we found that binding of the first ligand results in low but clear channel activation. Maximal agonist-induced activation is already apparent in tetramers harboring two or three wild-type TRPV1 subunits, which display comparable activity to wild-type tetramer. The non-vanilloid agonist 2-APB differs from that of capsaicin in the TRPV1 channel opening mechanism activating all S512F-mutated TRPV1 channels. Two or more wild-type TRPV1 subunits are also required for full anandamide-induced channel activation, a cannabinoid that shares overlapping binding-pocket to capsaicin. Our results demonstrate that the stoichiometry of TRPV1 activation is conserved for two types of agonists.